2020
DOI: 10.21512/tw.v21i2.6781
|View full text |Cite
|
Sign up to set email alerts
|

The Determinant Factors of KAI Access Awareness in PT. Kereta Api Indonesia from Millennial Generation Perspective

Abstract: PT. Kereta Api Indonesia (Persero), as a monopoly train company in Indonesia, launches KAI Access which has been downloaded by more than 5 million users, but only about 1,1 million users are active. The research intended to determine the relationship between brand experience, brand trust, perceived quality of customer satisfaction, and brand awareness in the minds of KAI Access consumers. The research used primary data with millennial populations by 986.775 and purposive sampling method with 400 KAI Access use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…This means that the higher the awareness of a brand, the higher the customer satisfaction. These findings are supported by previous research conducted by Lee (2022), Kartono & Tamami (2020), and Kusumah & Lee (2020) which found that Brand awareness is positively associated with customer satisfaction. This means that Tuku Coffee's customers who are familiar with the brand and find it appealing can experience satisfaction with their overall experience.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This means that the higher the awareness of a brand, the higher the customer satisfaction. These findings are supported by previous research conducted by Lee (2022), Kartono & Tamami (2020), and Kusumah & Lee (2020) which found that Brand awareness is positively associated with customer satisfaction. This means that Tuku Coffee's customers who are familiar with the brand and find it appealing can experience satisfaction with their overall experience.…”
Section: Discussionsupporting
confidence: 88%
“…High brand awareness increases the likelihood of customers choosing a specific brand, leading to increased customer loyalty in Korea's Franchise Coffee Shop industry (Lee, 2022). Similarly, the study by Kartono & Wildan Tamami (2020) emphasises that customer satisfaction shapes consumers' mindset and purchasing behaviour, ultimately contributing to brand awareness and repeat purchases at PT.KAI in Indonesia. (Kusumah & Lee, 2020) Finding that Green Brand Awareness positively influences customer satisfaction with Pristine 8+ packaged drinking water.…”
Section: Effect Of Brand Awareness Towards Customer Satisfactionmentioning
confidence: 98%
“…PT KAI perlu memperjelas proses ticketing untuk meminimalkan risiko pemesanan tiket, yang dapat mengurangi kepercayaan pelanggan (Suh et al, 2015). PT KAI sebaiknya meningkatkan kualitas KAI Acess karena terbukti mempengaruhi kepuasan pengguna KAI Access dan berdampak pada brand KAI Acess (Kartono & Wildan Tamami, 2020).…”
Section: Kepercayaan Penumpangunclassified
“…This, leaves a gap on why this app is not fully used or not chosen by downloaders. According to (Cordasco, 2016), there are four reasons why the intended users do not access the application, namely: 1) the application does not provide enough value for its users (Kartono & Tamami, 2020).…”
Section: Information Technology In Kai's Transformationmentioning
confidence: 99%